COUNSELING ON PREVENTION OF ARI INCIDENTS IN TODDLERS DUE TO PARENTS' SMOKING INTENSITY AT HOME IN THE WORK AREA OF PUSKESMAS MEDAN DENAI - Br Bukit, Herawati; Lubis, Fithri Handayani; Gurusinga, Mona Fitri (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Tobacco consumption is one of several risk factors for ISPA. Because of this, not only does the smoker put himself in risk, but so do all people around them, even those who don't smoke directly. It is possible to raise the incidence of acute respiratory infections (ARI) by 7.83 times in homes occupied by families that smoke compared to homes without smokers. The bulk of those who took the time to react are mothers with young children, mostly aged two or three. Research and conversations have led to this conclusion. Additionally, the majority of the parents who participated in the study smoke 11–20 cigarettes daily, and this demographic also includes the majority of the toddlers who were part of the study. This patient does not have ISPA, despite a statistical correlation between the preval_ence of heavy smoking at home and the incidence of the disorder in toddlers. Furthermore, a relationship has been established between the two. The administration of Puskesmas Medan Denai is expected to step up their efforts to reach out to families that smoke in the house and educate them. The possible health effects of smoking on family members, especially toddlers, in the Puskesmas Medan Denai neighborhood will be the focus of these programs. Cigarette smoking inside is advised in order to lessen the likelihood of health issues associated with ISPA disorders in children.